Essentials of medical biochemistry With clinical cases - Bhagavan, N. V.; Ha, Chung-Eun. (Amsterdam : Elsevier/Academic Press, 2011)
Essentials of Medical Biochemistry: With Clinical Cases encompasses the fundamental biochemical topics that relate to health and disease, and epitomizes a broad understanding of the mechanisms underlying numerous health problems. An extensive review and reference guide for students and experts alike, Essentials of Medical Biochemistry includes four-color illustrations throughout for the best visual representation of events and processes that occur at the molecular level of physiologic regulations, clinical effects, and interactions. --.
Useful for students in biochemistry, medicine, and other healthcare disciplines as a refresher to meet USMLE and other professional licensing examination requirements, as well as for experts in the field of basic research, Essentials of Medical Biochemistry includes clinical case studies and offers added study materials on an accompanying website, including interactive multiple-choice questions and supplementary information, to help users best understand the diagnosis, therapy, and monitoring of human diseases. --Book Jacket.
Includes bibliographical references and index.
Includes bibliographical references and index.
All age.
Keywords: Biochemical Phenomena; Cell Physiological Phenomena; Genetic Processes; Clinical biochemistry; Clinical biochemistry -- Case studies